"What kind of silence is being broken?": a visual-rhetorical history of the out-of-home placement of children in poverty in 1990s Belgium. (2nd November 2017) - Degerickx, Heidi; Roets, Griet; Rutten, Kris; Van Gorp, Angelo
Abstract: In this article it is assumed that the documentary impulse that gave the impetus to Courage, a photobook on people in poverty published in Belgium in 1998, is related to how the General Report on Poverty, published in 1994, accused the child welfare sector and protection services of having far too authoritative and coercive an approach. This article analyses Courage in relation to the issue of out-of-home placement of children in poverty following the framework proposed by Cara A. Finnegan in order to explore a rhetorical history of visual images. In this deductive approach the article pays attention to important moments in the life of photographs: production, reproduction, and circulation. This is combined with an inductive approach to generate a rhetorical understanding of the distinct generic characteristics of the visual artefact, in which attention is paid to the substantive as well as the stylistic characteristics of the images. The article attempts to analyse and explain systematically how symbolic acts and artefacts construe rhetorical processes on poverty, and explore how images of children and parents in poverty situations in the "rhetorical artefact" Courage can become "objects to think with".